Battery Performance Analysis of Solar Cell Powered Water Purification System: Case Study of Indonesian Army Polytechnic in Batu - East Java - Hidayat, Muhammad Iman; Mardiana, Diah; Srihardyastutie, Arie; Komara, Acep Nana (Jurnal Pembangunan dan Alam Lestari, 2025)
A solar cell-powered water purification system (SC-WPS) was developed and installed to generate clean water using renewable energy at the Polytechnic of the Indonesian Army (POLTEKAD). Developed and implemented using renewable energy from a 100 Wp solar panel, a solar cell-powered water purification system (SC-WPS) was designed to address this issue. The battery performance of the system is the primary focus of this work, encompassing battery discharge, state of charge (SOC), and key electrical parameters such as voltage, current, power, and solar irradiation data. Under test, the solar panel generated up to 495.7 Wh/day with a peak power of 93.28 W. Although the voltage remained between 12.78 V and 12.84 V, the battery depletion process showed stability; the total energy generated increased from 92.2 Wh in the first hour to 766.1 Wh by the tenth hour. Although the solar panel efficiency of the system peaked at 15.2%, factors such as uneven sunshine and energy loss caused it to decline over time. These results underscore the need to maximize battery capacity and solar panel efficiency to ensure continuous system operation for water purification in areas with varying sunshine levels. Keywords: battery performance, clean water, energy efficiency, Solar cell